Third Party Involvement in Verifying the Content of the Contract: A Comparative Study - Ouda, Hussam; Abdul Ridha, Hussein (Journal of Legal Sciences, 2026)
In some contracts, such as disposal contracts concluded by the legal or judicial representative of a minor, or sports contracts for professional athletes, or consumption contracts, the legislator grants others the authority to interfere with third parties in verifying their content by requiring approval or the possibility of challenging it after its completion. This study attempted to explain the idea of consent, its legal nature, the legal mechanisms through which the content of the contract can be challenged, and the parties that have the right to do so. It used the analytical approach and the method of comparative study with French law to benefit from its legislative and judicial provisions.